Collecting Duct Carcinoma of the Kidney - Dimopoulos, M.A.; Logothetis, C. J.; MARKOWITZ, A.; SELLA, A.; AMATO, R.; RO, J. (British Journal of Urology, 1993)
Summary— Collecting duct carcinoma (CDC) is a recently recognised histological variety of renal carcinoma (RC) considered to arise from the epithelium of the collecting ducts. Diagnosis of this entity depends on well defined gross and microscopic criteria and is supported by a characteristic immunostaining pattern. The clinical features of these patients, the natural course of the disease and its response to treatment have not been clearly established. Between 1980 and 1990 we treated 12 patients (median age 43 years, range 16–62) with collecting duct carcinoma of the kidney. In addition to being relatively young, each patient had a strong family history of associated malignancies. Survival was short (median 22 months) and 11 patients presented with locally advanced or metastatic disease. © 1993 British Journal of Urology